2024
DOI: 10.20944/preprints202402.0368.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Multi-strategy Enhanced Dung Beetle Optimization Algorithm and Its Application in Engineering

Huiqiang Zhang,
Ronghui Zhang

Abstract: This paper introduces a novel multi-strategy enhanced dung beetle optimization (MSDBO) algorithm that is designed to address several issues identified in the standard dung beetle optimization algorithm. Specifically, the MSDBO aims to enhance convergence speed, reduce susceptibility to local optima, and increase search accuracy. By incorporating three strategies: tent chaotic mapping for population initialization, the golden sinusoidal strategy for position updating, and the Lévy flight strategy for balancing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Although Xun proved the superiority of the DBO algorithm, it still has shortcomings, such as easily falling into local optima and poor global search ability. Therefore, many scholars have improved the DBO accordingly [16][17][18]. Fang et al suggested a DBO algorithm that merges quantum computing with multi-strategy (QHDBO), designed to prevent the algorithm from hitting local peaks through the t-distribution mutation approach in quantum computing, enhancing its convergence speed and optimization precision [19].…”
Section: Introductionmentioning
confidence: 99%
“…Although Xun proved the superiority of the DBO algorithm, it still has shortcomings, such as easily falling into local optima and poor global search ability. Therefore, many scholars have improved the DBO accordingly [16][17][18]. Fang et al suggested a DBO algorithm that merges quantum computing with multi-strategy (QHDBO), designed to prevent the algorithm from hitting local peaks through the t-distribution mutation approach in quantum computing, enhancing its convergence speed and optimization precision [19].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, based on the 'no free lunch' concept, it is impossible for a singular population intelligence optimization algorithm to address every optimization issue [23]. Every algorithm for optimizing population intelligence comes with its own set of limitations and constraints, leading numerous academics to suggest enhancements to these foundational algorithms [24][25][26]. These algorithms can compensate for the shortcomings of the original algorithms by integrating new strategies or the advantages of other algorithms to achieve better optimization results.…”
Section: Introductionmentioning
confidence: 99%